Active Site Mapping of Xylan‐Deconstructing Enzymes with Arabinoxylan Oligosaccharides Produced by Automated Glycan Assembly. Issue 13 (8th February 2017) - Senf, Deborah; Ruprecht, Colin; de Kruijff, Goswinus H. M.; Simonetti, Sebastian O.; Schuhmacher, Frank; Seeberger, Peter H.; Pfrengle, Fabian
Abstract: Xylan‐degrading enzymes are crucial for the deconstruction of hemicellulosic biomass, making the hydrolysis products available for various industrial applications such as the production of biofuel. To determine the substrate specificities of these enzymes, we prepared a collection of complex xylan oligosaccharides by automated glycan assembly. Seven differentially protected building blocks provided the basis for the modular assembly of 2‐substituted, 3‐substituted, and 2‐/3‐substituted arabino‐ and glucuronoxylan oligosaccharides. Elongation of the xylan backbone relied on iterative additions of C4‐fluorenylmethoxylcarbonyl (Fmoc) protected xylose building blocks to a linker‐functionalized resin. Arabinofuranose and glucuronic acid residues have been selectively attached to the backbone using fully orthogonal 2‐(methyl)naphthyl (Nap) and 2‐(azidomethyl)benzoyl (Azmb) protecting groups at the C2 and C3 hydroxyls of the xylose building blocks. The arabinoxylan oligosaccharides are excellent tools to map the active site of glycosyl hydrolases involved in xylan deconstruction. The substrate specificities of several xylanases and arabinofuranosidases were determined by analyzing the digestion products after incubation of the oligosaccharides with glycosyl hydrolases. Abstract : Automated glycan assembly enables characterization of glycosyl hydrolases : The automated glycan assembly of a collection of arabinoxylan oligosaccharides with diverse substitution patterns is reported. The synthetic arabinoxylan oligosaccharides were used for analyzing the substrate specificities of xylan‐degrading enzymes, which are critical reagents for biotechnological applications such as the production of second generation biofuels.